Precise cooperative sulfur placement leads to semi-crystallinity and selective depolymerisability in CS2/oxetane copolymers - Christoph Fornacon-Wood; Bhargav R. Manjunatha; Merlin R. Stühler; Cesare Gallizioli; Carsten Müller; Patrick Pröhm; Alex J. Plajer (Nature Communications, 2023)
Abstract CS2 promises easy access to degradable sulfur-rich polymers and insights into how main-group derivatisation affects polymer formation and properties, though its ring-opening copolymerisation is plagued by low linkage selectivity and small-molecule by-products. We demonstrate that a cooperative Cr(III)/K catalyst selectively delivers poly(dithiocarbonates) from CS2 and oxetanes while state-of-the-art strategies produce linkage scrambled polymers and heterocyclic by-products. The formal introduction of sulfur centres into the parent polycarbonates results in a net shift of the polymerisation equilibrium towards, and therefore facilitating, depolymerisation. During copolymerisation however, the catalyst enables near quantitative generation of the metastable polymers in high sequence selectivity by limiting the lifetime of alkoxide intermediates. Furthermore, linkage selectivity is key to obtain semi-crystalline materials that can be moulded into self-standing objects as well as to enable chemoselective depolymerisation into cyclic dithiocarbonates which can themselves serve as monomers in ring-opening polymerisation. Our report demonstrates the potential of cooperative catalysis to produce previously inaccessible main-group rich materials with beneficial chemical and physical properties.